Chemometric differentiation of Dipterocarpaceae wood species based on colorimetric measurements - Gibe, Monica; Abasolo, Willie P.; Sevilla, Fortunato III; Kalaw, Justine M. (2019)
The international trade of illegal timber often involves the misdeclaration of the wood species. A simple and reliable means for the differentiation of wood species could contribute to the control of this fraud. In this study, eight (8) commercially important and endangered dipterocarp timber wood species and mahogany were differentiated through colorimetric measurements carried out on hot water and ethanol extracts from the samples. Colorimetric measurements were done using a fabricated colorimeter that measured the absorption of blue, green, and red radiation. Chemometric analysis of the colorimetric data using principal component analysis (PCA) and hierarchical cluster analysis (HCA) revealed clustering, which enabled an efficient differentiation of the wood species. (Author's abstract)
Includes bibliographical references (pages 478-480)
Keywords: Forestry; Dipterocarps; Optical absorption; Pattern recognition; Wood extractives; Wood species differentiation